Recovery of genetic diversity levels of a Neotropical tree in Atlantic Forest restoration plantations - Sujii, Patricia Sanae; Schwarcz, Kaiser Dias; Grando, Carolina; de Aguiar Silvestre, Ellida; Mori, Gustavo Maruyama [UNESP]; Brancalion, Pedro H.S.; Zucchi, Maria Imaculada (Elsevier, 2017)
To support the long-term ecological viability of restoration projects, it is necessary to reach adequate levels of genetic diversity in spontaneously recolonizing and reintroduced populations. The importance of genetic diversity in the long-term viability of populations is acknowledged, but still poorly monitored in restoration projects. This study aimed to estimate the genetic diversity and inbreeding levels of populations of a tree species widely used in restoration projects in the Atlantic Forest of Brazil, Centrolobium tomentosum, exploring the potential of active restoration in successfully reestablishing populations with higher chances of long-term perpetuation in agricultural landscapes. We used both nuclear and chloroplast microsatellite markers to assess genetic parameters in juveniles and adult individuals in two high-diversity restoration plantations (28 and 60 years old), one disturbed fragment, and one large and well conserved protected area. We observed similar levels of genetic diversity and inbreeding, for juveniles and adults, in both restored and natural populations. Surprisingly, haplotype diversity was higher in restoration sites. We also found private alleles in juveniles in both restoration areas, and this is evidence of gene flow between restored and neighboring natural populations. However, we observed negative effects of inbreeding on the effective population size of populations from the disturbed natural remnant and restoration areas. These results provide evidence of the capacity of restoration plantations for recovering high levels of genetic diversity and the importance of maintaining large and well-conserved forest remnants to be used as seed sources for restoration efforts.
Keywords: Atlantic Forest; Centrolobium tomenstosum; Effective population size; Inbreeding; Population genetics